Partisipasi Perempuan Dalam Pembangunan Desa Di Kecamatan Kao Utara, Kabupaten Halmahera Utara - Djumati, Hunia; Rompas, Wilson Y; Rorong, Aries J (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTResearch carried out on women who are involved in development to see how big theircontribution in helping the development of the village in the district of North Kao.Research findings and the results of interviews with 12 respondents representing womenin rural development is quite good and significant. everyone involved in the process ofrural development projects in the district of North Kao, regardless of sex.Referring to the findings in this study, it is the sight of the need to be given somesuggestions, as follows: For the village and sub-district government and districtgovernment in general to always provide opportunities for women in developing the role ofparticipation in rural development in the district of North Kao. Then for women in order toincrease its role in rural development, particularly in terms of the savings rate in this studyhad a little infor- constraints.Keywords: Women's Participation in Rural Development dikecamatan North Kao, Districtnorth Halmahera